The Effect of Soya on Coconut Water-Egg Yolk Diluent at 3-4°C on Before Freezing Simmental Bull Sperm Quality - Mahyuda, Umi Jazilah Salsabila; Hariani, Dyah (LenteraBio : Berkala Ilmiah Biologi, 2023)
Storage of semen at low temperatures could a decrease to damage to spermatozoa due to coldshock, therefore a diluent with a function as a cryoprotectant is needed to protect spermatozoa, one of which is soy. This study aimed to determine the concentration of soy on coconut water-egg yolk basic diluent at a temperature of 3-4°C on the sperm quality of Simmental Bull before freezing. The research was used a completely randomized design with 5 treatments giving 0g soy concentration; 1.5g; 3g; 4.5g; and 6g were observed on storage for 2.5 hours, 5 hours, and 7.5 hours. There are 3 parameters , namely motility, viability, and membrane integrity. Parameters were observed using a light microscope with 400X magnification on a slide warmer at 37°C. Data were analyzed using Anova test and Duncan test. The results showed that there was a very significant effect when giving the concentration of soy in coconut water-egg yolk diluent on the sperm quality of Simmental Bull (P<0.05). Giving a 1.5 g soy concentration was the highest yield with motility (44.74±1.3%), viability (54.82±6.79%), and membrane integrity (44.74±1.3%. The conclusion of the study was that giving a 1.5g soy concentration on coconut water-egg yolk was the most optimal concentration that it could be applied in maintaining the sperm quality of Simmental Bull.